Effects of land application of raw and composted recycled paper mill sludge on Khaya senegalensis and Orthosiphon stamineus - Abdullah, Rosazlin (2013)
Recycled Paper Mill Sludges (RPMS) are complex mixtures of chemically recycled paper pulp, inorganic solid and chemical additives used in the paper manufacturing. These sludges are the final processed wastes from pulp and paper industries which are generated from different stages of papermaking. All paper industries produce sludge where disposal quantity is increasing every year which if not handled appropriately, led to environmental problem in the country. Since the usage of RPMS is restricted in Malaysia, studies on utilization of RPMS from Malaysian industries should be carried out to investigate the effect of RPMS on soil fertility, plant productivity and quality. The general objective of this study was to evaluate the effects of land application of raw and composted RPMS for agriculture and forestry applications in agroforestry system. Paper mill sludges have alkaline pHs ranging from 6.33 - 7.84 and thus can be important when utilized for acidic soil. Paper mill sludges contain total organic carbon ranging from 18.92 – 33.67% and organic matter content of 32.62 – 58.05% which can influence the biological, chemical and physical properties of soils. Paper mill sludges contain several essential plant elements including N (0.31 – 4.05%), P (0.02 - 0.08%), K (0.02 - 0.42%), Ca (0.36 - 1.28%) and Mg (0.41- 1.06%). In general, the concentrations of heavy metals (Cd, Cu, Ni, Mn, Pb and Zn) in the paper mill sludges did not exceed Class 2 of the categories proposed by British Columbia Pulp and Paper Association (2000). The spectrum of 13C NMR obtained in this study suggested that the RPMS exhibited peaks of cellulose and contains little lignin or hemicellulose like material. The FTIR spectrum complemented the structural information obtained in the 13C NMR spectrum. Similarly, environmental contaminants of harmful chemicals such as dioxins/furans and PAHs should not be of concern in RPMS as the levels were negligible. Therefore, RPMS can be safely used as a fertilizer or soil amendment for land application. Recycled paper mill sludge mixed with EFB fibres at 1:1 ratio was recommended to be suitable for land application in agriculture and forestry. From this study, the compost can be used as potting media and as soil conditioner enriched with plant nutrients or as a soil amendment to improve the biological, chemical or physical properties of a soil. Based on the potentially mineralizable N contents, double the rates of recommended inorganic fertilizer (300 and 200 kg N-1 of raw and RPM compost, respectively) were suggested for land application of Khaya senegalensis and Orthosiphon stamineus. Application of raw and RPMS compost produced higher dry matter yield and growth performance than the control treatments for Khaya senegalensis and Orthosiphon stamineus for glasshouse and field condition and were comparable to the inorganic fertilizer treatments. Based on carbon fractionation study, results after 1 year duration indicated that utilization of RPMS as organic amendment onto soil produced higher C and N contents in free and occluded light fraction (F-LF and O-LF) and particulate organic matter (POM). Meanwhile, the paper mill sludge application has significantly reduced the soil bulk density in the top soil which significantly affects the soil structure. However, the resonance peaks of any type of C structure in the soil remained completely unobservable even after removal of the magnetic materials followed by HF extraction. The FTIR spectra in soil at various time of sampling exhibited the same absorbance which indicates that no qualitative changes occurred during 6 months and 1 year of raw and RPMS compost application compared with the control treatments under glasshouse and field conditions. Total concentrations of Cu, Ni, Pb and Zn in soils were below the Investigation Level for Malaysian soils which the levels are taken at the 95th percentile of the heavy metals data for agricultural soils. Meanwhile, the concentrations of Cd are below the Australian Ecological Investigation Level (EILs) of 3 mg kg-1. Concentrations of heavy metals in leaves were below the MPC value of the Malaysian Food Act 1983 and Food Regulation 1985. In the fractionation study, cadmium was dominant in the exchangeable fractions. Meanwhile, Cu, Ni, Mn, Pb and Zn occurred in the residual fraction. Application of raw and composted RPMS to soil showed an increase of concentration of Cu, Mn, Zn, Ni, Pb and As in the leachates at 15, 30, 60 and 120 cm soil depths compared to the control in the following order, NO3- > Zn > Mn > Cu > Ni > Pb > Cd. The concentration of NO3-, Cd, Cu, and Zn were below the established threshold value for drinking water by World Health Organization (WHO, 2008) guideline, which is the international guideline adopted by Malaysia. However, concentrations of Mn, Ni and Pb values were found to exceed the threshold value of WHO (2008) regulations. Therefore, heavy metals in the leachates need to be monitored until no more of these metals are released from the treated soil. This study indicated that using raw RPMS with addition of EFB (1:1) was able to improve the structure of raw RPMS as a compost product and potential as organic fertilizer to substitute for the inorganic N fertilizer. Hopefully, this research can be used as preliminary information and reference on utilization of raw and RPMS compost as soil amendment for land application especially in Malaysia.